Case report: Novel germline c.587delA pathogenic variant in familial multiple endocrine neoplasia type 1 - Huang, Haotian; Li, Jianwei; Zhang, Kun; Tang, Yu; Zhang, Min; Fan, Zhen; Wang, Tao; Liu, Yaoxia (Frontiers in Endocrinology, 2024)
Multiple Endocrine Neoplasia type 1 (MEN1) is a rare genetic disease, characterized by co-occurrence of several lesions of the endocrine system.In MEN1, the pathogenic MEN1 gene mutations lead to the Abnormal expression of menin, a critical tumor suppressor protein. We here reported a case of a 14-year-old male with insulinoma and primary hyperparathyroidism. Genetic testing demonstrated a novel heterozygote variant c.587delA of MEN1, resulting in the substitution of the 196th amino acid, changing from glutamic acid to glycine, followed by a frameshift translation of 33 amino acids. An identical variant was identified in the proband's father, who was further diagnosed with hyperparathyroidism. To the best of our knowledge, this is the first report of MEN1 syndrome caused by the c.587delA MEN1 variant. Observations indicated that, despite sharing the same MEN1 gene change, family members exhibited diverse clinical phenotypes. This underscored the presence of genetic anticipation within the familial context.